Nonlinear Optical Properties of Discotic Hexylthiotruxene Derivatives - Kumar Manish; Perumbilavil Sreekanth; Vinayakumara D. R.; Goel Alok; Philip Reji; Kumar Sandeep (American Chemical Society, 2025)
The search for efficient and transparent nonlinear optical (NLO) media has led to the investigation and development of alternative organic optical materials. In this context, a series of new hexylthiotruxene derivatives have been synthesized, and their linear and NLO properties are explored. These truxene derivatives show large NLO absorption due to their C3 symmetry, presence of large hyperpolarizability, and extended π-conjugation. Herein, we show that two-photon absorption and three-photon absorption processes are the main cause of nonlinear absorption in these materials under 5 ns and 100 fs excitations at 532 and 800 nm excitations, respectively. The nonlinear absorption coefficients have high values of 2 to 7.9 × 10–10 m/W in the nanosecond domain and 2.2 to 7.4 × 10–21 m3/W2 in the femtosecond domain. The corresponding nonlinear absorption cross-section (δ) values and the nonlinear susceptibilities were also calculated from the numerically obtained nonlinear absorption coefficient values. Tailored truxene derivative showed an excellent optical limiting threshold of 4.5 J/cm2 and is comparable to or better than most recently reported and benchmark optical limiting materials. Longer alkyl members of the series showed the largest nonlinear absorption in both excitation domains and could be a potential optical limiter.